Effect of recasting on the elastic modulus of metal-ceramic systems from nickel-chromium and cobalt-chromium alloys - Mirković Nemanja (Vojnosanitetski Pregled, 2007)
Background/Aim. Elastic modulus of metal-ceramic systems determines their flexural strength and prevents damages on ceramics during mastication. Recycling of basic alloys is often a clinical practice, despite the possible effects on the quality of the future metal-ceramic dentures. This research was done to establish recasting effects of nickel-chromium and cobalt-chromium alloys on the elastic modulus of metalceramic systems in making fixed partial dentures. Methods. The research was performed as an experimental study. Six metal-ceramic samples of nickel-chromium alloy (Wiron 99) and cobalt-chromium alloy (Wirobond C) were made. Alloy residues were recycled through twelve casting generations with the addition of 50% of new alloy on the occasion of every recasting. Three- point bending test was used to determine elastic modulus, recommended by the standard ISO 9693:1999. Fracture load for damaging ceramic layer was recorded on the universal testing machine (Zwick, type 1464), with the speed of 0,05 mm/min. Results. The results of this research revealed significant differences between elasticity modules of metal-ceramic samples in every examined recycle generation. Recasting had negative effect on the elastic modulus of the examined alloys. This research showed the slight linear reduction of elastic modulus up to the 6th generation of recycling. After the 6th recycling there was a sudden fall of elastic modulus. Conclusion. Recasting of nickelchromium and cobalt-chromium alloys is not recommended because of the reduced elastic modulus of these alloys. Instead of reusing previously recasted alloys, the alloy residues should be returned to the manufacturer. .